Shared decision-making in patient education: An observational study of possible workplace bias - Egill Atlason 1982- (2021)
Introduction: Patient-centered education is an important part of physical therapy. The difference in value and implementation of patient-centered education practices between workplace settings of physical therapists in Iceland has not been examined. Objective: To examine perceived importance and use of patient-centered care through shared decision-making by comparing responses of physical therapists in three different workplace settings (hospital, rehabilitation, private practice) in Iceland. Methods: A cross-sectional, web-based survey was completed by 216 physical therapists (PTs), with a response rate of 35,1%. Closed ended statements that utilized the “three-talk” method of shared decision-making were examined and results measuring frequency of use and perceived importance were compared between different workplace settings. Results: The results indicated that PTs in rehabilitation frequently value and use the “three-talk” method of shared decision-making more frequently when compared to PTs at the hospital or PTs in private practice. Frequency of responses from all participants indicated a less use of the “option” and “decision” parts of the “three-talk” model during the shared decision-making process. A difference of over 43% was observed in a collaborative practice statement when comparing “importance of” to “use of” statement in a clinical setting. Gender and work experience were determined not to have any effect on the findings of this study according to Kruskal-Wallis test results. Conclusion: There does appear to be a difference in the use of and perceived importance of patient education between workplace settings of physical therapists when utilizing shared decision-making. Continued efforts are needed to train and encourage PTs to use shared decision-making in practice, especially in the area of collaboration with the patient on treatment goals.